NRG/ErbB signaling regulates neonatal muscle growth but not neuromuscular contractures in neonatal brachial plexus injury. Issue 5 (28th January 2021) - Ho, Brendan L.; Goh, Qingnian; Nikolaou, Sia; Hu, Liangjun; Shay‐Winkler, Kritton; Cornwall, Roger
Abstract : Neonatal brachial plexus injury (NBPI) causes disabling and incurable muscle contractures that are driven by impaired growth of denervated muscles. A rare form of NBPI, which maintains afferent muscle innervation despite motor denervation, does not cause contractures. As afferent innervation regulates various aspects of skeletal muscle homeostasis through NRG/ErbB signaling, our current study investigated the role of this pathway in modulating contracture development. Through pharmacologic modification with an ErbB antagonist and NRG1 isoforms, we discovered that NRG/ErbB signaling does not modulate the development of contractures in neonatal mice. Instead, ErbB inhibition impeded growth in nondenervated skeletal muscles, whereas increased ErbB activation exacerbated denervation‐induced skeletal muscle atrophy. This potential regulatory effect of NRG/ErbB signaling on neonatal muscle growth warrants deeper investigation. Abstract :